La Gestión del GAD municipal de Riobamba y la generación del comercio justo en los beneficiarios de los planes de desarrollo. - Pasto Chimbolema, Noreliz Mayerlin (2023)
The purpose of this research is to determine the management of the Riobamba Municipal Government and its influence on the generation of fair trade in the beneficiaries of development plans. The target population used was thirty producers and entrepreneurs who are part of Plaza Vida, located at Sesquicentenario Park, Alfaro Plaza, and Politécnica. The technique used in this research work was the survey and the interview corresponding to its instruments, the survey questionnaire, and the interview guide, which were provided to the producers and entrepreneurs of Plaza Vida by the researchers. The interview was conducted, with the manager in charge of fair trade. The methodology used resulted in frequency and percentages data. A low performance in the Riobamba Municipal Government management was identified, where limitations were observed concerning producers and entrepreneurs, there was no proper socialization of the programs reflected in the PD y OT. The study concludes that there is a relationship between the municipality of Riobamba and the generation of fair trade in the beneficiaries of the development plans, as a result, a model of administrative management is proposed to promote the principles of fair trade in the Riobamba citizens.